EDUCATIONAL VALUES IN THE QURAN SURAH AL JUMUAH - Evi Febriani; Nurilah Zahirotin; Pupita Maharani; Radhita Sabrina Filzah; Peni Okti Yani; Pika` Nurmala (Program Pascasarjana UIN Sumatera Utara, 2024)
For those who study and believe in the Qur'an, the sacred book of Muslims, the divine revelations found within provide guidance, instruction, and educational resources. As mentioned in QS. al-Jumu'ah verses 1-5, the Qur'an, which forms the foundation of Islamic teachings, has several qualities, one of which is the importance of education. In many schools today, the Qur'an and the sunnah are not the primary sources of knowledge. Because the Islamic aim of education has not been fully realized, students have a tendency to become materialistic and distant from high principles. Thus, the goal of this research is to examine the educational principles included in verses 1-5 of QS. al-Jumu'ah and ascertain the mufasirs' perspectives on these principles. Similar to library research, this study employs a qualitative technique and applies the tafsir tahlili and muqoron procedures to analyze the data. According to the study's findings, the six mufasirs examined interpreted QS. al-Jumu'ah verses 1-5 similarly, emphasizing the Prophet's mission to educate his people, self-purification from Allah, and a parable for those who do not put their knowledge into practice. The educational ideals included in QS. al-Jumu'ah verses 1-5 include tawhid, worship, and morals.